2004
DOI: 10.1007/s00442-004-1547-x
|View full text |Cite
|
Sign up to set email alerts
|

Competitive interactions in macroinfaunal animals of exposed sandy beaches

Abstract: The influence of biotic interactions in structuring macroinfaunal communities of exposed sandy beaches, an unstable habitat characterized by strong physical forces, is generally considered negligible. We investigated the hypothesis that competitive interactions during burrowing could potentially affect the intertidal distribution and abundance of macroinfaunal animals of sandy beaches using two species of invertebrates, a hippid crab, Emerita analoga, and a bivalve, Mesodesma donacium, common along the coast o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 37 publications
1
31
1
2
Order By: Relevance
“…The enhanced ability of juveniles to cope with low salinities may represent an early physiological trait allowing larvae to settle in vacant areas by active or passive processes (e.g. Mann et al 1991, Shanks & Brink 2005) and thereby to reduce strong intraspecific and interspecific competition for food and habitat quality (Tarifeño 1980, Dugan et al 2004 and increasing recruitment success. However, contradictory evidence regarding spatial segregation related to salinity has been reported by Ortiz & Stotz (1996).…”
Section: Reproductive Cyclementioning
confidence: 99%
“…The enhanced ability of juveniles to cope with low salinities may represent an early physiological trait allowing larvae to settle in vacant areas by active or passive processes (e.g. Mann et al 1991, Shanks & Brink 2005) and thereby to reduce strong intraspecific and interspecific competition for food and habitat quality (Tarifeño 1980, Dugan et al 2004 and increasing recruitment success. However, contradictory evidence regarding spatial segregation related to salinity has been reported by Ortiz & Stotz (1996).…”
Section: Reproductive Cyclementioning
confidence: 99%
“…Defeo et al (1997) reported maximum densities of Excirolana armata similar in allopatry and sympatry, but allopatric populations of E. braziliensis were more abundant lower on the shore than at sympatric locations, where distribution was restricted to upper beach levels. McLachlan (1998) and Dugan et al (2004) provided further evidence of the role of competitive interactions in experiments where changes in burrowing performance of one species were monitored at different densities of other species, even though these effects could be minimal at field densities (McLachlan 1998). Yu et al (2002) found that feeding habits in 4 sublittoral amphipods could explain variations in zonation; when dietary composition overlapped, spatial segregation reduced competition for food.…”
Section: Spatial Structure and Patch Dynamicsmentioning
confidence: 99%
“…Active filtering of larvae during feeding activity was a potential explanatory mechanism. Dugan et al (2004) demonstrated negative relationships between the mole crab Emerita analoga and the surf clam Mesodesma donacium at small spatial scales. Spatial overlap in the intertidal distributions of these species varied with abundance in time and space.…”
Section: Microscale Patternsmentioning
confidence: 99%
“…In fact, some authors, including, Dugan et al (2004), believe that biological interactions, including competitive ones, not only affect the distributions and zonation of intertidal macro-infauna but potentially also community structure. Studies by Veloso and Cardoso (2001) show that the abundance of the communities was also not related to any physical parameter and these authors suggested that certain biotic factors, such as food source, recruitment, predation and competition, are responsible for the differences in macrofaunal densities between beaches.…”
Section: Discussionmentioning
confidence: 99%